Bank to sovereign risk spillovers across borders: Evidence from the ECB's comprehensive assessment - Johannes Breckenfelder; Bernd Schwaab (European Central Bank (ECB), 2018)
We study spillovers from bank to sovereign risk in the euro area using difference specifications around the European Central Bank's release of stress test results for 130 significant banks on October 26, 2014. We document that following this information release bank equity prices in stressed countries declined. Surprisingly, bank risk in stressed countries was not absorbed by their sovereigns but spilled over to non-stressed euro area sovereigns. As a result, in non-stressed countries, the co-movement between sovereign and bank risk increased. This suggests that market participants perceived that bank risk is shared within the euro area.
Keywords: C68; F34; 330; bank-sovereign nexus; risk spillovers; stress test; European Central Bank; Comprehensive Assessment